Awareness and acceptance of various contraceptive methods among postpartum women in a tertiary care center - Jaiswal, Jyoti; Naik, Smrity; Rangari, Ratna; Sinha, Ashish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: This study was conducted to know awareness and acceptance of contraceptive methods among post-partum women in the tertiary care centre of Chhattisgarh. Methods: A cross-sectional interview-based study was conducted on a sample of 440 post-partum women. The interview included socio demographic profile, awareness and acceptance of contraceptive methods in postpartum period and factors affecting its use. Results: In our study, we observed that 95.9% were aware of some method of contraception. This knowledge increased with increasing education, socioeconomic class. 90.9 % accepted one of the contraceptive methods during their hospital stay. The most common contraceptive method chosen was IUCD (80.8%). Major source of information was health care worker (83.88%). The main reason for non-acceptance of contraception was fear of side effects. Conclusions: High level of persistent motivation is required, so initiation of motivation regarding post-partum contraception should be done in antenatal visits and reinforcement in post-partum period should be done. Proper counseling regarding possibility of milder side effects and way of coping with them should be reinforced, continued motivation and reassurance will give positive attitude for acceptance of contraception. Reinforcement of awareness in society (family and friends/neighbor) this may give positive impact on awareness and acceptance. There is need of couple counseling for better acceptance. Emphasis is required for involvement of men/head of the family for it.